The electromagnetic response of composition-regulated honeycomb structural materials used for broadband microwave absorption. (20th October 2021) - Pang, Huifang; Duan, Yuping; Dai, Xuhao; Huang, Lingxi; Yang, Xuan; Zhang, Tuo; Liu, Xiaoji
Graphical abstract: Highlights: Honeycomb structural materials are developed to obtain broad bandwidth absorption without weight increasing. The composition is regulated to optimize the absorbing performance. Magnetic resonation is found for the first time in honeycomb structure, which is beneficial to the microwave attenuation. Simulation is performed to analyze the electromagnetic response when structure converses from solid to honeycomb. Effective absorption bandwidth of 9.8 GHz is obtained in the fabricated honeycomb structural materials. Abstract: The undesirable absorption bandwidth is the main limitation for the application of microwave absorbing materials. Noting that the design of structure and composition of absorbing coating allows it to obtain a satisfying absorption bandwidth and to avoid weight increasing, honeycomb and its sandwich structures coated by various absorbant have been developed and measured using an arch measurement system over 2−18 GHz. To further understand the absorption mechanisms of honeycomb structural materials, simulation based on finite element method and transmission line theory is performed to analyze the different responses to the applied microwave between honeycomb structural materials and uniform-medium slab materials. The proper composition design allows control over the microwave loss mechanisms, which optimize the coating to possess both of the dielectric and magnetic advantages. For the honeycomb structural materials, the magnetic resonation is found for the first time, which is resulting from the periodic honeycomb walls on both sides of the dielectric cavity (consisting of the aramid paper interlayer and vacuum hexagonal prisms). In addition, the conversion of structure from solid to honeycomb brings about changes in impedance, propagating path, effective wavelength, effective attenuation area, microwave phases, and inductive coupling effect, etc., which result in a better microwave absorbing performance. The honeycomb sandwich structure coated by CIP/CB/EP with the weight ratio of 4:0.03:1 shows the absorption bandwidth of ∼9.8 GHz for reflection loss (RL) lower than -10 dB which covers part of the S and C bands and almost the whole X and Ku bands.